식료품공장폐수의 효율적 관리를 위한 조사 연구 - 조규석 (연세대학교 보건대학원, 1988)
[한글] 식료품제조가공업은 그 공장수가 많고 대체로 폐수량이 많으며 생산품목이 다양하므로 수질오염방지를 위한 효율적인 관리가 더욱 요구되고 있다. 본 연구는 한강본류 및 북한강 수계에서 '87년말 현재 정상조업을 하고 있는 183개 식료품제조공장을 대상으로 식료품공장폐수의 각 업종별 폐수량, 오염도, 오염부하량, 폐수 처리방법, 처리효율, 처리수의 분석항목간 상관성등의 특성을 조사·분석한 결과 다음과 같은 결과를 얻었다. 1. 폐수배출량이 많은 업종은 조미료 및 식품첨가물제조업(1,795.8 m**3/일), 전분 및 당류제조업(889.1 m**3/일)등 주로 화학적 공법으로 제품을 제조하는 공장들이며, 특히 도축, 빵과자 및 국수제조, 전분 및 당류제조, 조미료 및 식품첨가물 제조업체에서는 고 농도의 폐수 (BOD로서 1,000㎎/ℓ이상)를 배출하고 있음을 알았다. 2. 식료품공장의 폐수를 효율적으로 처리하기 위해서는 폐수량이 1일 1,000 m**3 이상 이거나 원폐수의 BOD 농도가 800㎎/ℓ인 경우에는 생물학적처리법 또는 종합적처리법이 주로 적용되고 있었다. 3. 폐수처리시설의 정상가동상태를 간편하게 확인하기 위하여 COD (Xc)의 측정치로 BOD (Y^^B)값을 다음식에 의거 예측할 수 있었다. (1) 낙농품제조가공업 Y^^B1 = 1.58 X^^C1 - 15.2 (r=0.849) (2) 동식물유지제조업 Y^^B2 = 1.368 X^^C2 - 8.21 (r=0.924) (3) 빵과자 및 국수제조업 Y^^B3 = 1.319 X^^C3 - 8.18 (r=0.913) (4) 도축시설 Y^^B4 = 1.203 X^^C4 + 1.58 (r=0.848) (5) 두부 및 유사식품제조업 Y^^B5 = 1.244 X^^C5 + 1.12 (r=0.896) 이상의 결과를 종합하여 보면 오염부하량이 많은 업종은 과실 및 채소가공, 조미료 및 식품첨가물질제조, 전문 및 당류제조업 등인데 폐수처리시설의 운영관리는 물론 설계·시공을 할 때에도 세심한 배려가 요청된다. 그리고 주로 화학적 공법으로 제조하는 식품공장에 대하여는 특별관리업종으로 지정 관리되어야 할 것이다. [영문] This study was performed on the 183 facilities of food-processing industries, which were operating in the basin of the main Han-River and the north Han-River, for the effective management of their wastewater. There were sub-devided into 12 kinds of industries and studied on the 6 items for them, The items used in this study were amount of wastewater, concentration and amount of pollutans in raw wastewater, treatment process and efficiency of wastewater treatment, correlation between BOD, COD and SS values of wastewater. The results were as follows: 1. Amount of wastewater from the manufacture of condiments and food-additive products was 1,795.8 m**3/day the most large amount of it among them. And the second large amount of wastewater was discharged from the starch and sugar products manufacture. 2. The industries which average concentration of BOD as above 1,000㎎/ℓ in the raw wastewater, were manufacture of slaughtering of livestock and poultry, bakery products, starch and sugar, and condiments and food-additive products. 3. The BOD removal efficiency in the wastewater treatment plants of consolidated treatment and biological treatment was 95.0% and 93.9%, respectively. 4. The correlation coefficients(r) between BOD and COD values in treated wastewater of industries were COD(X) and the proposed correlation for the treated wastewater were as follows: (1) Manufacture of dairy products Y^^B1 = 1.58 X^^C1 - 15.2 (r=0.849) (2) Manufacture of vegetable and animal oils and fats Y^^B2 = 1.368 X^^C2 - 8.21 (r=0.924) (3) Manufacture of bakery products Y^^B3 = 1.319 X^^C3 - 8.18 (r=0.913) (4) Slaughtering of livestock and popultry Y^^B4 = 1.203 X^^C4 + 1.58 (r=0.848) (5) Manufacture of bean curd and similar foods ^^B5 = 1.244 X^^C5 + 1.12 (r=0.896) 5. Amount of BOD discharge from the manufacture of canning and preserving of fruits and vegetables was 52㎏ per unit product, which was the highest.
환경관리학과/석사